Influence of different rootstock-interstock-scion combinations on mango (Mangifera indica L.) traits - Jain, Shikha; Prakash, Jai; Singh, Sanjay Kumar; Kumar, Chavlesh; Srivastav, Manish; Singh, Kanhaiya; Pandey, Renu; Sharma, Sandhya; Singh, Anshuman; Kumari, Ishu (Frontiers in Plant Science, 2025)
Mango (Mangifera indica L.), a highly valued tropical fruit, faces challenges in productivity due to the use of non-descriptive rootstocks and large tree architecture. To address this, a field experiment was conducted at ICAR-IARI, New Delhi (2021-2024), using Olour as rootstock and scion, with three grafting combinations: without interstock, with Amrapali interstock, and with Mallika interstock. The study aimed to evaluate their effects on morpho-physio-chemical traits, leaf and soil nutrient content, and anatomical parameters. The results revealed significant differences in plant performance based on the treatment combinations. The Olour/Mallika/Olour combination showed the highest leaf width (3.71 cm),intercellular CO2 concentration (356.20μmole m-2 s-1), net photosynthetic rate (8.51 μmole m-2 s-1), leaf total soluble protein (4.34 mg/g FW), leaf total sugars (119.05 mg/g FW), total chlorophyll (4.04 mg/g FW), total carotenoid (0.22 mg/g FW) and stomatal density (746.00 mm-2) and lowest apical bud phenols (1014.31 mg/100 g) and leaf proline content (0.36 µg g-1 FW). Conversely, the Olour/Amrapali/Olour combination exhibited lowest rootstock girth(7.11 mm), scion girth (4.32 mm), leaf fresh weight (1.26 g), leaf dry weight (0.40 g), leaf net photosynthesis (3.50 μmole m-2 s-1), leaf total soluble protein (1.25 mg/g FW), total chlorophyll (1.65 mg/g FW), total carotenoid (0.13 mg/g FW) and stomatal density (380.75 mm-2) and demonstrated higher proline (1.06 µg g-1 FW) and apical bud phenols (3067.53 mg/100 g)indicating dwarfing potential. Among the single-graft combinations, Amrapali/Olour exhibited moderate vigour and nutrient content, while the Mallika/Olour combination maintained high stomatal conductance and favourable growth traits. These findings confirm that both interstock and direct scion-rootstock combinations significantly influence plant physiology and nutrient dynamics. Anatomically, stomatal density and the complexity of the area were also significantly affected by the choice of interstock. Overall, these findings highlight the important role of interstocks in modifying plant vigour, physiology, and nutrient acquisition. Future studies are needed to assess the long-term field performance of these combinations under various agro-climatic conditions.